2012
DOI: 10.1016/s0019-4832(12)60093-5
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery embolisation

Abstract: A B S T R A C TPurpose of study: Fibroids are commonest benign tumour of the uterus. It presents with bleeding per vagina in most of the cases. Surgical treatment consists of myomectomy or hysterectomy with or without salpingo oophrectomy, with its inherent morbidity, prolonged hospital stay and psychosocial problems. Surgery is not the best option especially in unmarried and nullipara. Materials and methods:Thirty-five patients were subjected to uterine artery embolisation (UAE).Mean age was 35.51 ± 7.36 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Failed therapy was reported among 2 females, one of which needed hysterectomy 6 weeks after the procedure and another requiring myomectomy 6 month after the procedure. All these findings were like what was reported by Bhardwaj R, et al [17]. Where authors found that fibroids disappeared in 8 out of 35 patients (22.9%), decreased in size by > 75% in 11 patients (31.4%), and by 50-75% in 6 patients (17.1%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Failed therapy was reported among 2 females, one of which needed hysterectomy 6 weeks after the procedure and another requiring myomectomy 6 month after the procedure. All these findings were like what was reported by Bhardwaj R, et al [17]. Where authors found that fibroids disappeared in 8 out of 35 patients (22.9%), decreased in size by > 75% in 11 patients (31.4%), and by 50-75% in 6 patients (17.1%).…”
Section: Discussionsupporting
confidence: 89%
“…Exclusion criteria included: Uterine malignancy, severe allergy to iodinated contrast media, subserosal pedunculated fibroids, recent or ongoing pelvic inflammatory disease, adenomyosis cases, post-partum haemorrhage cases and presence any contraindication to interventional radiology. The targeted sample was 150 women to estimate an average reduction after embolization in the fibroid size by about 50%-75% [17], with precision of 7% at 95% confidence level. The sample women will be selected consecutively from those who attended the interventional radiology department during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…If advancement past the vaginal or ovarian branch proves challenging, a micro coil is strategically placed at the origin of the unit [10]. When no significant opacification of the ovarian or vaginal team was observed, additional contrast was administered, followed by embolization at this catheter location [11]. The embolization procedure prioritized using particles first, followed by gel foam, with meticulous documentation of the volumes employed for each patient [12].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical treatment options range from use of drug therapy, surgery, and uterine artery embolization (UAE). Treatment of AM uterine artery embolization is a novel approach that not only can ease the symptoms of dysmenorrhea, be able to retain the uterus, and have very clear short-term effects, but it still requires further in-depth evaluation regarding the recurrence rate, lesion vascular recanalization, and its influence on ovarian and reproductive function with longer-term studies [3,4].…”
Section: Introductionmentioning
confidence: 99%